COL4A1 and COL4A2 Mutations Analyses with Perinatal Arterial ?schemic Stroke - Ozan Koçak; Kursat Bora Carman Bora Carman; Coskun Yarar; Hirofumi Kodera; Hirotomo Saitsu; Naomichi Matsumoto (Baiman Bauntung Batuah Center, 2020)
Perinatal arterial ischemic stroke (PAIS) is one of the frequent causes of mortality and morbidity, but its etiology remains unclear. COL4A1 and COL4A2 mutations are monogenetic causes of weakness of the basement vascular membranes resulting in cerebral small-vessel disease, cerebral hemorrhage, and porencephaly. We hypothesized that variations in the COL4A1 and COL4A2 genes cause PAIS and performed mutation screening of these genes in 17 PAIS patients by whole-exome sequencing. Clinical, demographic, and laboratory data of the 17 PAIS patients were obtained by evaluating hospital files retrospectively. Patients included in the study were invited to the clinic for COL4A1 and COL4A2 mutation analysis. Results: The patient group consisted of 13 females (76.5%) and four males (23.5%) with a mean age of 107.4 ± 11.5 months. Maternal/fetal and prothrombotic risk factors identified in 52.9% and 94.1% of the patients, respectively. Whole-exome sequencing analysis did not reveal COL4A1 and COL4A2 pathological mutations in any of the patients. Although we did not find an association between PAIS and COL4A1 and COL4A2 variations, we believe that new studies with larger patient populations may reveal such a relationship.